2022
DOI: 10.1177/00033197221110715
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between High-Sensitivity C-Reactive Protein/Albumin Ratio and Cardiovascular Prognosis in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Limited studies have focused on the impact of high-sensitivity C-reactive protein (hsCRP) to albumin ratio (CAR) on cardiovascular outcomes in patients undergoing percutaneous coronary intervention (PCI). Hence, the present study evaluates the association between CAR and cardiovascular outcomes in patients undergoing drug-eluting stent (DES) implantation. We consecutively enrolled 9375 CHD patients undergoing DES implantation. All patients were divided into 3 groups according to their CAR: tertile 1 (CAR ≤.02,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“… 26 Finally, a study of 9375 patients with coronary heart disease receiving drug-eluting stent implantation also found that CAR was an independent predictor of the occurrence of adverse cardiovascular events and myocardial infarction. 27 Our findings are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 94%
“… 26 Finally, a study of 9375 patients with coronary heart disease receiving drug-eluting stent implantation also found that CAR was an independent predictor of the occurrence of adverse cardiovascular events and myocardial infarction. 27 Our findings are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…In other recent investigations, CRP was not considered the sole marker but rather in interaction with other factors. In a Chinese study, the importance of CRP to albumin ratio as an independent predictor of major adverse cardiac and cerebrovascular events and MI CVD patients was highlighted ( n = 9375, follow-up period = 2 years) [ 40 ]. In another large-scale prospective cohort study, the elevation of both Lp(a) and CRP was associated with a significantly higher risk of major adverse cardiac and cerebrovascular events ( n = 10,424; follow-up period = 5 years) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, abnormal lipid metabolism, abnormal function of immune cells, and inflammatory cytokine release are associated with CAD prognosis. Yang has demonstrated that MACCEs and MI in patients receiving PCI are independently predicted by the ratio of high-sensitivity C-reactive protein to albumin [27]. IL-1β is involved in pancreatic cell destruction and can be used to predict CVD risk in people with T2DM [28].…”
Section: Discussionmentioning
confidence: 99%